Correlation between general health, nutrition, and oral health status of elderly in a typical retired community-house - Kusumawardani, Banun; Dharmayanti, Agustin Wulan Suci; Robin, Dwi Merry Christmarini; Rahayu, Yani Corvianindya; Fitriyana, Nurul Isnaini (Universitas Padjadjaran, 2021)
Introduction: Indonesia is in an aging population era marked by an increase in elderly population above 7%. An enhancement of elderly population presents health problems due to organ function deterioration and requires extraordinary attention. General health, nutrition, and oral health status are the most problems claimed by elderly, particularly retired. Objective of this study was to analyze the correlation between the general health, nutrition, and oral health status of elderly. Methods: Analytical descriptive research with cross sectional method was carried out on 36 respondents in Paguyuban Purnabakti, Patrang, Jember, East Java Province. The sampling was done by purposive sampling. Information about social-demography and general health status of respondents were obtained from the questionnaire. The social-demography investigation comprised sex, age, education level and status of residence. While general health observation, it comprised smoking status, general check-up, presence of systemic diseases, blood pressure and blood biochemical parameters.[CS1] Nutritional status was examined by body mass index (BMI). Oral examination for identifying oral health status included the number of the teeth remaining in the oral cavity, use of dentures, oral hygiene index (OHI-s), and periodontal tissue health (CPITN). Results: The result exhibited that most of the respondents presented good general health status. However, there was no significant correlation between routine general health observation and age (p=0.906). Moreover, there was no significant relationship between blood biochemical profile (blood glucose, total cholesterol, and blood pressure level) with nutrition status (p=..., p=..., and p=... respectively), and oral health status (p=...), except with oral hygiene (p=...). Conclusion: This study is limited to Paguyuban Purnabakti, Patrang, Jember, East Java Province. Although this study could not be generated in all communities, this study concluded no relationship between general health (smoking, systemic disorders, and routine general health observation), nutritional status, and oral health in the elderly. [CS1]Disesuaikan dengan table 2